Community Perception of the Usage of Urban Public Transport and Online Application Based Transportation in South Tangerang - Rissa Hanny; Syafieq Fahlevi Almassawa (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
Public transportation services in Indonesia in general and the city of South Tangerang are still low; schedules are unclear, facilities are dirty, unsafe, unprofessional vehicle crews, and fares are not cheap. This study presents the results of a study on the perceptions of the people of South Tangerang city towards the use of city transportation and the perceptions of online-based transportation. This research is qualitative research with data collection methods using deep interviews or in-depth interviews with parties related to this study, such as urban transportation users and online-based transportation users. Interviews are also conducted on other stakeholders such as the government, 'Organda,' transportation companies online. In addition to interviews, this research also uses FGD (Forum Group Discussion), carried out with the community and related instant. Other information is obtained by researchers from discussion forums of various parties to see what the wider community wants in fulfilling their transportation needs. The result of this research is that the community's perception towards urban public transportation is still not good because the service is still bad; because of this, people get another alternative, namely online transportation.